THE EFFECT OF SMS REMINDER ON THE BEHAVIOR OF CONSUMING FE TABLETS IN PREGNANT WOMEN - Siti Mulyani; Nurbaeti Amilia; Magdalena Agu Yosali; Emilya Irawan; Nuraidah Nuraidah; Eni Rizki Rahayu (Universitas Respati Yogyakarta, 2023)
This study aims to determine the effect of SMS reminder on the behavior of consuming Fe tablets in pregnant women. This type of pre-experimental research with one group pretest-posttest design used a questionnaire on the behavior of pregnant women in consuming Fe tablets before and after being given treatment in the form of SMS Reminder. Research carried out BPM Nelli Herawati Bogor Regency with a sample of 32 respondents with a total sample. The data analysis technique used statistical tests with the simple paired t test. Before the SMS reminder was given, from 32 respondents, 17 (53.1%) had negative behavior in consuming Fe tablets and 15 (46.9%) respondents with positive behavior in consuming Fe tablets. Meanwhile, after receiving SMS remainder for 1 week in a row, 13 (40.6%) respondents with negative behavior in consuming Fe tablets and 19 (50.4%) respondents with positive behavior in consuming Fe tablets. The results of the simple paired t test statistic obtained a p value of 0.000 (p value <0.05). There was an effect of SMS reminder on the behavior of consuming Fe tablets in pregnant women